Illegal Immigration and Race Superiority across the Globe: Lessons for the African Union - Kazeem Oyedele Lamidi; Hammed Adetola Adefeso; Costa Hofisi (E-Journal of Humanities, Arts and Social Sciences)
Governance plays a critical role in shaping rural development outcomes, acting both as an enabler and a constraint to sustainable livelihoods. Although rural development research in Uganda has focused mainly on financial input, less attention has been paid to institutional and governance dynamics that determine how resources are mobilised, allocated, and translated into tangible benefits for rural communities. This study contributes to the rural livelihood discourse by examining the governance structures and practices in the southwestern districts of Isingiro and Kisoro through a qualitative approach involving 34 Key Informant Interviews (KIIs) and four Focus Group Discussions (FGDs). Guided by Institutional Theory and Network Governance Theory, the study reveals that although governance frameworks, such as those set out in Uganda’s Local Government Act of 1997, formally empower sub-national units to engage in planning, budgeting, and service delivery, their implementation is significantly hindered by institutional capacity constraints, centralised fiscal control, and political interference. The findings also highlight the importance of informal governance mechanisms, such as the locally respected “L.C. Zero” structures, which operate outside the formal state architecture yet play a vital role in community-level decision-making and accountability. These insights underscore the need for governance reforms that strengthen institutional capacity, promote locally grounded accountability mechanisms, and foster collaborative networks between state and non-state actors to support resilient and inclusive rural development.